The Impact of Company Size and Profitability on Firm Value with Institutional Ownership as a Moderating Variable - Hidayatulloh, Ilham Rachmat; Trisnaningsih, Sri (Yayasan Ilomata, 2024)
A nation's manufacturing sector is vital to its economic development. Firm value is the main worry for investors and management in the face of the global competitiveness and the Covid-19 epidemic. As a result, this study looks at how profitability and company size affect the company's value, with institutional ownership serving as a moderator. Quantitative research methodology is employed, and secondary data from 63 industrial sector manufacturing organizations listed on the IDX is the type of data used. From this population, 22 samples of companies were collected to be tested. SEM-PLS was used to test the data. The findings demonstrated that while profitability has no bearing on business value, company size does. The impact of company value is not mitigated by institutional ownership on the relationship between firm size and profitability. These findings suggest that a big business will have the chance to grow its worth. However, strong profitability does not always translate into higher solid worth. Because it has limited control over management performance, institutional ownership is unable to regulate the relationship between the two, which permits fraud to occur and affect the scale and profitability of the business. Managers and investors can utilize this research to evaluate and augment a company's value in order to stimulate the economy of the country, especially for manufacturing enterprises in the industrial sector that are listed on the IDX.